A case of impacted central incisor due to dentigerous cyst associated with impacted compound odontome - Jayam, Cheranjeevi (BMJ Publishing Group, 2014)
Odontomes are hamartomatous growths of odontogenic origin. Odontomes usually do not erupt into oral cavity and can cause several difficulties like swelling, displacement of teeth and adjacent structures, cystic changes and carcinomatous transformation. Odontomes are treated by surgical removal. Dentigerous cysts arise due to accumulation of fluid between reduced enamel epithelium and crown of unerupted tooth. Dentigerous cysts cause several difficulties such as swelling, non-eruption of involved teeth and displacement of adjacent teeth, thus requiring early detection and prompt treatment. Treatment for dentigerous cyst ranges from marsupialisation to enucleation. In children, marsupialisation is more commonly used when compared with enucleation treatment. This study discusses successful treatment of impacted central incisor due to obstruction from dentigerous cyst originating from impacted compound odontome. The paper also throws light into importance to radiography while diagnosing odontome.